Analisis Penggunaan Metode Ceramah dan Tanya Jawab pada Materi Rububiyyah di Pondok Pesantren MIs Al Azhar Lil Mukhtarin Medan - M. Hafiz Harza; Mawaddah Nasution (EduInovasi: Journal of Basic Educational Studies, 2024)
Tawhid is a word that is familiar to Muslims. Because in general we want or even claim to be a monotheist. However, it is possible that there are still many people who do not understand the nature and position of monotheism for human life, even those who already feel monotheistic. Starting from the many people's understanding of the nature of monotheism and forgetting about its high position, it is very important to convey a clear explanation of this issue. The learning process is the process of transferring knowledge from teacher to student, and appropriate methods are needed to ensure that knowledge given is fully accepted. At first glance, the importance of learning methods in the teaching and learning process is central for teachers in choosing learning methods that suit their students' personalities and optimizing and minimizing the advantages of the learning methods used by teachers in the classroom. We must realize that each learning method definitely has its own advantages and disadvantages. -each.  This research used descriptive qualitative methods which were carried out at the Mis Al Azhar Lil Mukhtarin Islamic Boarding School. The aim of this research is to find out how to apply rububiyyah material to students, instill the values ​​of monotheism in students, how to use the question and answer method and lectures in learning that takes place in the classroom.  The results of this research were that combining these two methods proved to be the most effective, with questions and answers strengthening understanding through active interaction and lectures providing a strong theoretical basis. By combining these two approaches, teaching tauhid rububiyyah can become more holistic, covering various aspects of learning and meeting the needs of different students.